Hubungan antara komitmen, keselamatan kerja dan kinerja karyawan PT. BEHAESTEX Bagian Produksi Cabang Kediri - Agus Dwi Prasetyo; Setyabudi Indartono (JURNAL ILMU MANAJEMEN, 2014)
Globalization changes every thing very quickly. Company’s problem to improve performance indicated become more complex. Individual performances are needed to be payed in attention for management level to improve it. Commitmentandwork safety are indicated to affect employee’s performance. This study aims to determine the effecton the safety and commitment on employee performance. PT. BEHAESTEX Kediri Branch Production Department was choosen tobe a sample for this study case. The results demonstrate that commitment and safety influence employee performancepositively.